Perlindungan Hak Asasi Lingkungan dalam Sistem Hukum Tata Negara Indonesia - Mardiyati, Siti (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The right to a healthy environment is part of human rights that must be guaranteed by the state. In the Indonesian constitutional law system, the protection of environmental human rights has been accommodated in various legal instruments, including the constitution and laws and regulations. This article aims to analyze how the protection of environmental human rights in Indonesia's constitutional law system, by reviewing the legal basis, policy implementation, and challenges in its enforcement. Using a normative method and a statutory approach, this study finds that despite strong regulations, there are still challenges in the implementation and enforcement of laws related to the protection of environmental human rights.